NMT for sustainable and environmentally friendly tunnelling in Nepal - Panthi, Krishna Kanta (Journal of Nepal Geological Society, 2025)
Recent weather pattern in Nepal indicates that there is a considerable impact on the weather system, which is believed to be due to both global and regional warming. The change in weather has started causing serious damage in the Himalayan region and elsewhere. The debate on the minimization of carbon emission through reduced use of fossil fuel has been ongoing for some couple of decades. However, the carbon emission caused by the production of cement and concrete has been less discussed and highlighted. In addition, unnecessarily excessive use of cement and steel is counterproductive due to increased project costs. Therefore, there is a strong need for the reduction in the use of construction material consisting cementitious and steel products while developing the infrastructure and hydropower projects in Nepal where use of underground space will be extensive in near future. Use of Norwegian Method of Tunnelling (NMT) could serve as an alternative to the reduced use of cement, concrete and steel products. This Key-Note lecture highlights the principals used in Norwegian Method of Tunnelling (NMT), benefit it gives in the reduced use of concrete and steel, which helps to optimize project costs, contributes to reduce emission and assists to enhance sustainable development of infrastructure and hydropower projects in Nepal.